2001
DOI: 10.1097/00000539-200111000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Medical Information on the Perioperative Course of Stress in Cardiac Surgery Patients

Abstract: The quantity of stress during transport to the operating room and the perioperative psychoendocrinologic course of stress in combination with two different methods of preoperative medical information are described in 60 consecutive patients awaiting cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…However, some controversy still remains, since for cardiac surgery, information delivered either personally or by pamphlets produced no benefit [9][10][11] . It is also interesting to note that any complete or minimal written information regarding anesthesia, while not significantly changing the state-anxiety levels, could increase the knowledge regarding anesthesia 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some controversy still remains, since for cardiac surgery, information delivered either personally or by pamphlets produced no benefit [9][10][11] . It is also interesting to note that any complete or minimal written information regarding anesthesia, while not significantly changing the state-anxiety levels, could increase the knowledge regarding anesthesia 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides being indifferent to the patients' needs, such material does not aid anxiety control 9 . Patients from this sample with the correct information about surgery had reduced anxiety regardless the diagnosis information (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bergmann et al [5] and Schuldham et al [28] found no significant difference in scores between patients guided or not on the same disorder before the surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Bergmann et al [5] found that the anxiety level decreased significantly in the postoperative period in a study that aimed to assess the effects of oral information preoperatively combined with greater personal attention given by the surgeon on the levels of stress, anxiety and welfare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation